Contribution of the Brazilian Institute of Information in Science and Technology to the promotion of Open Access and Open Science: analysis of its infrastructures - Campos, Fhillipe de Freitas (2023)
Introduction: Historically, scientific communication was dominated by a marketing logic in which oligopolies of commercial scientific publishers charged high fees so that researchers could have access to the scientific publications of their peers. Given the unsustainability of this market on the part of the scientific community, the Open Access Movement emerged at first and, more recently and with new contributions, Open Science. Faced with this context and aware of the competences for which it was instituted, the Brazilian Institute of Information in Science and Technology (Ibict) began to create infrastructures, projects and actions aimed at achieving the precepts defended by the aforementioned Movements. Objective: Indicate and describe the scientific communication actions, projects and infrastructures created and coordinated by Ibict in the context of Open Access and Open Science. Methodology: This article is characterized by documentary research with a qualitative approach. Since, analyzes were developed from the most varied types of sources. Results: The main results show that since the beginning of the 2000s, Ibict has been working firmly to build the necessary infrastructures to promote Open Access and, more recently, Open Science. This effort is reflected in the presentation of the 14 actions, projects and infrastructures that were created and coordinated by or in partnership with the Institute. Conclusions: The presented infrastructures denote the effort undertaken by Ibict to promote scientific communication in an open and transparent manner. Complementary to each other, such infrastructures are capable of creating a national framework in favor of the pillars of Open Access and Open Science, highlighting Brazil in the international scenario.